Yoga for Every Body: Experts say yoga can ease pain and improve mobility for people with neurologic conditions. And a disability is no reason not to try it. Issue 2 (April 2016) - Griffin, Katherine
Abstract : Experts say yoga can ease pain and improve mobility for people with neurologic conditions. And a disability is no reason not to try it.